Novel surface generation and characterisation by electrochemical jet processing - Speidel, Alistair (2018)
Electrochemical jet processing (EJP) is an applied electrochemical technique capable of exercising highly localised control of material removal independent of mechanical properties. This makes the process suitable for both micromachining and surface texturing operations in high-value engineering materials, without altering the near-surface in a thermomechanical manner. The research presented in this thesis primarily investigated the generation and characterisation of topographies arising from EJP, since topography can strongly affect functional and mechanical properties of the material. It was found that the resulting surface texture was directly influenced by the starting material microstructure, even in processing regimes beyond which the microstructure was thought to make a difference. This was proposed to be the result of the high flow velocities in EJP. In addition, under appropriate processing regimes, the microscale topography is sensitive to underlying microstructural characteristics such as orientation, localised composition, defect density and thermal history. This was applied to develop a large-area microstructural characterisation technique, which when calibrated against a conventional approach, is capable of identifying localised crystallographic texture. This was applied to common engineering materials such as nickel, aluminium alloys and copper. The second objective of the thesis was to innovate the geometry of processed features. Conventionally, material removal is shown to be a transformation of the Gaussian energy distribution within the electrolyte jet. Through small additions of doping agents, the low energy area, responsible for tapering of the machined feature, can be reduced. This leads to an increase in precision and dimensional accuracy. In addition, it is shown that individual corrosion pits can be propagated, which represents the development of a novel form of electrochemical processing, capable of further reducing the scale of this micromachining process, as well as easily generating fractal surface patterning. In addition, the thesis explores the viability of EJP as a coating technology. This was firstly observed through electroplating operations, where a high level of control over the deposit morphology was demonstrated through electrolyte design. Subsequently a methodology was presented regarding the co-deposition of particulate matter within a metallic deposit. Finally, EJP was presented as a route through which more robust surfaces with interesting functional properties could be generated as part of an in-jet plasma electrolytic oxidation process.